2003
DOI: 10.51347/jum.v7i2.3905
|View full text |Cite
|
Sign up to set email alerts
|

Fractal assessment of street-level skylines: a possible means of assessing and comparing character

Abstract: Fractal analysis and the calculation of fractal dimension offers the potential for the numerical characterization of places by providing a synthetic measurement of place complexity. This paper provides a fractal analysis of street-scale urban skylines, linking the calculation of fractal dimension to the presence of the physical features making up a skyline. A technique for calculating skyline fractal dimensions is presented and suggestions are made about the use of fractal analysis in comparing the character o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Silhouette complexity and fractal dimension are two typical morphological indicators that have been widely used in skyline-related studies. Silhouette complexity evaluates the skyline from the perspective of its overall orientation (Niu and Li, 2013; Heath et al, 2000b; Mak et al, 2005), whereas the fractal dimension describes the skyline in terms of micro variation (Cao and Zhang, 2013; Cooper, 2003; Hagerhall et al, 2004). Therefore, these two indicators are calculated, and the results are shown in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Silhouette complexity and fractal dimension are two typical morphological indicators that have been widely used in skyline-related studies. Silhouette complexity evaluates the skyline from the perspective of its overall orientation (Niu and Li, 2013; Heath et al, 2000b; Mak et al, 2005), whereas the fractal dimension describes the skyline in terms of micro variation (Cao and Zhang, 2013; Cooper, 2003; Hagerhall et al, 2004). Therefore, these two indicators are calculated, and the results are shown in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde fraktal geometri ile mimarlık, planlama alanlarının birlikte değerlendirildiği çalışmalar oldukça sınırlı sayıdadır. Mevcut olan çalışmalarda ise, daha çok kent makroformu, kentsel gelişim ve sokak siluetleri konuları üzerine yoğunlaşılmıştır (Cooper, 2003;Hagerhall, 2004;Mcadams, 2007). Sokak ölçeğinde fraktal geometri ile mekânsal zenginliği analiz eden çalışmalar oldukça sınırlı sayıdadır.…”
Section: Bulgularunclassified
“…When the national and international literature is examined, it is seen that the studies in which fractal geometry and the fields of architecture and planning are evaluated together are quite limited. While some of the existing studies focus on urban macro form, urban development, and street silhouettes (Cooper, 2003;Hagerhall, 2004;Mcadams, 2007), some focus on spatial richness with fractal analysis at the street scale (Jacobs, 1961;Gehl, 1987;Montgomery, 1998;Taylor, 1999;Oskrochi, 2008;Kacha et al 2013;Akbarishahabi and Tekel, 2017). In these studies, especially focusing on spatial richness and fractal geometry, it has been revealed that fractal dimension is an important indicator of spatial richness, and it has been concluded that as the level of visual diversity in images increases, the fractal dimension increases.…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, however, there remains considerable uncertainty about the processes in operation (Batty and Longley, 1988). More recently, fractals have been applied to urban design and form, attempting to measure and compare features important in understanding the complexity and character of places (Cooper, 2003(Cooper, , 2005Robertson, 1992). It is confidently asserted that the everyday environment is fractal (Crompton, 2001).…”
Section: Computers and Urban Morphologymentioning
confidence: 99%